Peran Peran Kesadaran Wajib Pajak dalam Memediasi Pengaruh Pemahaman dan Edukasi Pajak terhadap Kepatuhan Wajib Pajak : (Studi Kasus Wajib Pajak KPP Pratama Blora) - Erni Ernanda; Bayu Kurniawan (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the extent to which the role of taxpayer awareness mediates the understanding of taxation and tax education activities on taxpayer compliance in individual taxpayers under the supervision of KPP Pratama Blora refers to the phenomenon of declining levels of taxpayer compliance, which can be seen from the decline in the number of SPT submissions each year. Data processing is done quantitatively by utilising Structural Equation Modeling techniques through the Partial Least Square approach. A total of 100 respondents were used in this study, which were obtained using an accidental and willing sample selection technique.The findings in this study indicate that tax understanding has a significant impact on taxpayer awareness, but does not show a significant influence on the level of tax compliance. On the other hand, tax education was shown to influence taxpayer awareness, but did not contribute directly or through awareness in improving compliance. Taxpayer awareness is shown to have a significant impact on compliance and serves as an effective mediator between understanding and compliance. Based on the results of this study, it is important to improve the quality of education and tax education that is more participatory and communicative to build the level of awareness and compliance of taxpayers at KPP Pratama Blora.